(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The current study focused on the development of novel potentially active anti-microbial agents based on the benzimidazole-acetamide system. A novel series of various substituted benzimidazole- N- phenyl acetamides was synthesized through a feasible scheme characterized by IR, Proton nuclear magnetic resonance (1HNMR), and MASS spectral methods. All the synthesized compounds were screened for anti-bacterial activity against two gram-positive strains: Staphylococcus aureus, Bacillus subtilis; four gram-negative strains: Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa, and Klebsiella pneumonia; and anti-tubercular activity against mycobacterial strain: Mycobacterium tuberculosis. Among the 15 compounds (6a–6o) tested, three compounds, 6e, 6f, 6l, and 6m demonstrated high potency with MIC values ranging from 6.25–12.5μg/mL against both gram-positive and gram-negative strains. In addition, compounds 6e, 6f, and 6l displayed the highest anti-tubercular activity with a MIC value of 25μg/mL.